2019
DOI: 10.3390/biom9090456
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PD-L1 Expression Status between Pure-Solid Versus Part-Solid Lung Adenocarcinomas

Abstract: Although lung adenocarcinomas (LADs) with ground-glass opacity (GGO; part-solid tumors) have been shown to differ from those without GGO (pure-solid tumors) in clinicopathological features and prognoses, whether programmed death ligand-1 (PD-L1) protein expression differs between these two tumor types is unclear. This study included 124 patients with clinical T1a–c LAD who received pulmonary resections during 2007–2009. The E1L3N antibody was used to stain for PD-L1 in primary LAD specimens. The specimens were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
7
10
0
Order By: Relevance
“…Nelson et al observed differential immune cell infiltration and PD-L1 expression in adenocarcinoma presenting as GGOs compared with solid lesions in a CT scan (8). Lung adenocarcinoma with GGO was correlated with a lower incidence of PD-L1 expression than pure-solid tumors (9). In our case, following a complete reduction in the size and density of almost all the remaining GGOs 12 months after pneumonitis, we presumed that all the GGOs had a similar TMB or TIME.…”
Section: Discussionsupporting
confidence: 54%
“…Nelson et al observed differential immune cell infiltration and PD-L1 expression in adenocarcinoma presenting as GGOs compared with solid lesions in a CT scan (8). Lung adenocarcinoma with GGO was correlated with a lower incidence of PD-L1 expression than pure-solid tumors (9). In our case, following a complete reduction in the size and density of almost all the remaining GGOs 12 months after pneumonitis, we presumed that all the GGOs had a similar TMB or TIME.…”
Section: Discussionsupporting
confidence: 54%
“…We clearly showed that the incidence of PD-L1 expression was much lower in GGOs than pure-solid tumors in several articles, which was verified by Suda et al. in a clinical experiment including 124 qualified patients (4% vs. 25%, p < 0.01) ( 32 ). Wu et al.…”
Section: Discussionsupporting
confidence: 69%
“…There was only one article (33) that provided details in the subgroups, so a meta-analysis could not be performed on the subgroups. Still, it was shown in the articles that the rate of PD-L1 expression was significantly lower in GGOs (4.44%-14.16%) than solid nodules (18.36%-35.04%) in the same cohorts (9,(31)(32)(33).…”
Section: Pd-l1 Expressionmentioning
confidence: 96%
“…This study reveals the immunological differences between these two types of lung adenocarcinomas. Additionally, the results of this report provided an important speculation regarding the prognostic impact of PD-L1 expression in lung adenocarcinomas, which had been controversial in previous studies [ 5 ]; the ratio of tumors with GGO, which are associated with favorable prognosis, will determine the apparent prognostic implication of PD-L1 expression in a cohort [ 4 ]. The second paper on this topic is a review article written by Fujimura et al [ 6 ].…”
mentioning
confidence: 91%
“…Among these six papers, three are classified into topic (i) evaluating the immunological status of cancer/the tumor microenvironment. The first study is from our group, which reported that PD-L1 expression is significantly lower in lung adenocarcinomas with ground-glass opacity (GGO) compared with those without GGO (pure-solid tumors) [ 4 ]. This study reveals the immunological differences between these two types of lung adenocarcinomas.…”
mentioning
confidence: 99%